DESKRIPSI KAPAL INDUK DENGAN JENIS DEK LANDASAN TAKE OFF DAN LANDING PESAWAT TEMPUR - Endro Tri Susdarwono (Fakultas Sains dan Teknologi Universitas Karimun, 2022)
An aircraft carrier is a warship that functions as an air base at sea, equipped with a full-length flight deck and facilities for carrying, arming, deploying, and recovering aircraft. the type of runway deck takes off and landing of fighter aircraft, while the type of research applied in this research is descriptive qualitative research. Data collection and analysis methods in this study apply the use of existing data. The data collected consists of various documents, books, manuscripts, mass media, websites or journals. Related to data collection, internet-based research is applied. Extracting information from various trusted sources is applied including electronic documents, reputable online journals, official websites of news agencies and government institutions. The study concluded that the flight deck of an aircraft carrier is one of the most exhilarating and dangerous working environments in the world (not to mention one of the harshest). The deck may look like a regular ground runway, but it works very differently, due to its smaller size. Aircraft operating from aircraft carriers operate in two distinct ways: conventional aircraft that roll on deck for takeoff and landing, although usually assisted by launch and capture equipment; and vertical/short takeoff and landing (V/STOL) aircraft, which are capable of using thrust vector control (TVC) to take off and recover vertically or after very short landings.